Our unrequited love for natural ingredients - Burdock, George A.; Wang, Wendan (Food and chemical toxicology, 2017)
Naturally sourced food ingredients have been the beneficiary of legal, regulatory and consumer preference as the result of a widely shared assumption of safety. However, the natural substances consumed in modernity may have little to do with the historically consumed part of the plant or even the plant itself. Further, our initial impression of a safe plant derivative may well be false as the result of the use of different growth conditions or, changes in harvesting and processing conditions that may have brought about a higher level of toxic constituents. Despite the variability of plant constituents, manufacturers' standards are set according to the content of commercially desirable properties, rather than presence of potentially toxic constituents. Why then, after all the potential reservations regarding naturals, is there such an enmity toward synthetic chemicals (including single chemical fermentation products), which have been tested in a systematic manner for potential toxic effects and whose composition is well known as the result of consistent manufacturing techniques and analytical controls? The authors will describe the paradigms used for natural products safety review and compare them with the safety criteria required for an “artificial” food ingredient. •A brief summary of the arguments for and against the adoption of laws permitting the use of the GRAS concept as it applies to synthetic substances (and single chemical entity fermentation).•A comparison of the requirements for demonstrating safety of natural substances vs synthetics and single chemical fermentation products.•A brief description of non-regulated toxins produced by commonly consumed foods.•A reminder of a broken promise by FDA to review foods for safety, originally waived through because of other priorities.